Pristop k longitudinalnemu študiju uporabnikov COBISS - Pivec, Franci (Knjižnica, 1996)
The studies of the bibliographic information systems users correspond to the studies of library users and are an indispensable condition for the optimization and quality of work of these systems. In choosing between the traditional and constructivistic paradigm we have decided for the latter which in turn requires also the use of corresponding research methodologies. The main components, relations and elements of the study of bibliographic systems users have been derived from an extensive Slovene and international bibliography, and they will become an object of comparative research also in the case of the COBISS users. The research plan covers a period of five years, and the cooperation of two research institutions of Maribor University as well as research contributions of Slovene librarians, is expected.
Keywords: Vzajemni katalogi; Slovenia; Slovenija; Knjižnice; Uporabniki; Študije; COBISS; COBISS.net; knjižnični informacijski sistemi